Genome-wide identification and analysis of anthocyanin synthesis-related R2R3-MYB genes in Cymbidium goeringii - Chen, Jiating; Bi, Yuan-Yang; Wang, Qian-Qian; Liu, Ding-Kun; Zhang, Diyang; Ding, Xiangqing; Liu, Zhong-Jian; Chen, Shi-Pin (Frontiers in Plant Science, 2022)
The MYB gene family plays a vital regulatory role critical in plant metabolism, stress response, and floral colour. The R2R3-MYB gene family of C. goeringii was identified, and its expression was analysed using bioinformatics in this article. The R2R3-MYB genes of Arabidopsis thaliana were used as a reference to determine 104 CgMYB genes and categorize them into 22 subfamilies. Exon/intron organizations and conserved motif analysis revealed that the majority of CgMYB genes were highly conserved, and chromosome localization and collinearity analysis provided evidence of tandem duplication and segmental duplication events, indicating the phenomenon of gene family expansion and contraction. The function of CgMYB genes was analysed by cis-acting element and GO enrichment. In addition, three CgMYB genes were selected for RT‒qPCR, suggesting the CgMYB91 association with the formation of red spots on the labellum. In short, this study provides a comprehensive and specific function of the R2R3-MYB transcription factors in orchids. Further verification experiments are needed to explore the CgMYB genes related to the colour regulation of C. goeringii.